Test of the nursing minimum data set: availability of data and reliability - Devine, E C; Werley, H H (Research in nursing & health, 1988)
An initial study of the availability of the elements in the Nursing Minimum Data Set (NMDS) and intercoder reliability across four types of clinical settings is reported. These clinical settings included an acute care hospital, a nursing home, a home health care agency, and two ambulatory care clinics. The health records of 116 randomly selected subjects were reviewed to determine the availability of the NMDS elements. A randomly selected subset of 23 of these records provided data on intercoder agreement. All but four of the NMDS elements were available for 85% or more of the subjects. The average intercoder agreement across all NMDS elements was a satisfactory 91%. However, the intercoder agreement on some NMDS elements was much lower, suggesting a need to refine the definitions and procedures for collecting some of the NMDS elements. Where appropriate, coefficient Kappa and Pearson product moment correlation statistics for reliability are reported on individual NMDS elements.